2022
DOI: 10.1002/hpm.3486
|View full text |Cite
|
Sign up to set email alerts
|

“If we can just dream…” Māori talk about healthcare for bipolar disorder in New Zealand: A qualitative study privileging Indigenous voices on organisational transformation for health equity

Abstract: Objectives: This paper identifies barriers to equity and proposes changes to improve the organisation of healthcare in New Zealand for Māori with bipolar disorder (BD) and their families. Design: A qualitative Kaupapa Māori methodology was used. Twenty-four semi-structured interviews were completed with Māori with BD and members of their family. Structural and descriptive coding was used to organise and analyse the data, including an analytic frame that explored participants' critique of attributes of the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, previous research has found initiatives targeted towards improving individual staff cultural safety, while necessary, are unlikely to be sufficient to improve culturally safe and equitable care within health services (Curtis et al, 2019). It is imperative that there is also an organizational and system-level focus on prioritizing the importance of te ao Māori and hauora Māori, and an emphasis and expectation of the delivery of culturally safe and equitable care (Curtis et al, 2019;Haitana et al, 2022aHaitana et al, , 2022bHaitana et al, , 2023. We are hopeful the establishment of Te Aka Whai Ora (the Māori Health Authority) and the partnership model intended within NZ's health and disability system reforms will serve as an important starting point for this necessary 'topdown' prioritization (Ministry of Health, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research has found initiatives targeted towards improving individual staff cultural safety, while necessary, are unlikely to be sufficient to improve culturally safe and equitable care within health services (Curtis et al, 2019). It is imperative that there is also an organizational and system-level focus on prioritizing the importance of te ao Māori and hauora Māori, and an emphasis and expectation of the delivery of culturally safe and equitable care (Curtis et al, 2019;Haitana et al, 2022aHaitana et al, , 2022bHaitana et al, , 2023. We are hopeful the establishment of Te Aka Whai Ora (the Māori Health Authority) and the partnership model intended within NZ's health and disability system reforms will serve as an important starting point for this necessary 'topdown' prioritization (Ministry of Health, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of the recent SDHB Mental Health Continuum of Care Review (Synergia, 2021) which indicated a need for SDHB SMHAS to shift away from a dominant Western 'medical model' of health and well-being, and instead utilize more holistic mental health and well-being models. Recent qualitative research exploring effective and culturally appropriate care for Māori SMHAS users, particularly those with bipolar disorder, has shown the importance of incorporating te ao Māori, tikanga Māori (customs/ protocols), and involving whānau (family) in service delivery for Māori SMHAS users (Haitana et al, 2022a(Haitana et al, , 2022b(Haitana et al, , 2023Staps et al, 2019); approaches/elements which the 'medical model' has been described as incongruent with (Bush et al, 2019;Durie, 2011;Graham & Masters-Awatere, 2020;Haitana et al, 2022aHaitana et al, , 2022bStaps et al, 2019). Reports from some participants of an absence of Māori models of care in their workplace, suggests that increased utilization of Māori health models and clinical practice frameworks, such as Kaupapa Māori frameworks (Haitana et al, 2022a), Te Whare Tapa Whā (Durie, 1985), the Meihana model (Pitama et al, 2007), Te Ara Waiora a Tāne (Bush et al, 2019) and Mahi a Atua (Kopua et al, 2020), may be an important step in improving the quality of care for Māori SMHAS users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase utilised the quantitative and qualitative findings from the two earlier phases of the project and distributed them to focus group participants. Focus groups were then undertaken with staff involved in the design and delivery of healthcare services for Māori patients with BD in New Zealand [10,11,[25][26][27]. This component of the study aimed to discuss the evidence about patterns of health service use and Māori patient experiences with focus group participants, and to draw on their expertise as healthcare professionals to develop guidelines for best practice for Māori with BD and generate strategies for change to address areas of unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…Just funding more services and doing more of the same will make mental health access worse, as the increase in funding will make it worthwhile for parents of less severe adolescents to engage with services and persist more to obtain access. International data has consistently shown that factors such as lower incomes, poor housing ,unemployment and discrimination are all associated with psychological distress (Mulder et al, 2022, Hatiana et al, 2022, Allison et al, 2019. The rise in psychological distress is therefore socially determined, and not amenable through simple mental health interventions, such as therapy or antidepressant medication (Allison et al, 2019).…”
Section: Implications For Policymentioning
confidence: 99%